Interaction of Green Polymer Blend of Modified Sodium Alginate and Carboxylmethyl Cellulose Encapsulation of Turmeric Extract - Sa-Ad Riyajan; Janthanipa Nuim (International Journal of Polymer Science)
Turmeric extract (tmr) loaded nanoparticles were prepared by crosslinking modified carboxylmethyl cellulose (CMC) and modified sodium alginate (SA) with calcium ions, in a high pressure homogenizer. The FTIR spectra of CMC and SA were affected by blending due to hydrogen bonding. The negative zeta potential increased in magnitude with CMC content. The smallest nanoparticles were produced with a 10 : 5 SA/CMC blend. Also the release rates of the extract loading were measured, with model fits indicating that the loading level affected the release rate through nanoparticle structure. The 10 : 5 SA/CMC blend loading with tmr and pure tmr showed a good % growth inhibition of colon cancer cells which indicate that tmr in the presence of curcumin in tmr retains its anticancer activity even after being loaded into SA/CMC blend matrix.